Daniel goes on an egg hunt - Testa, Maggie (Daniel Tiger's neighborhood., 2023)
"In this Pre-Level 1 Ready-to-Read, Daniel Tiger goes on an egg hunt! How many eggs can Daniel find in the annual egg hunt? And what colors will they be? This adorable concept book introduces young readers to numbers and colors."--